2016
DOI: 10.1093/glycob/cww128
|View full text |Cite
|
Sign up to set email alerts
|

Diverse subcellular localizations of the insect CMP-sialic acid synthetases

Abstract: The occurrence and biological importance of sialic acid (Sia) and its metabolic enzymes in insects have been studied using Drosophila melanogaster. The most prominent feature of D. melanogaster CMP-Sia synthetase (DmCSS) is its Golgi-localization, contrasted with nuclear localization of vertebrate CSSs. However, it remains unclear if the Golgi-localization is common to other insect CSSs and why it happens. To answer these questions, Aedes aegypti (mosquito) CSS (AaCSS) and Tribolium castaneum (beetle) CSS (TcC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The single Drosophila sialyltransferase has been functionally and biochemically characterised [50,51]. In other insect species, sialyltransferase genes have been identified and parts of the CMP-sialic acid biosynthesis pathway revealed [52,53]; however, only upon glycoengineering can it be safely concluded that Lepidoptera will express sialic acid on recombinant glycoproteins [54].…”
Section: Sialic Acidsmentioning
confidence: 99%
“…The single Drosophila sialyltransferase has been functionally and biochemically characterised [50,51]. In other insect species, sialyltransferase genes have been identified and parts of the CMP-sialic acid biosynthesis pathway revealed [52,53]; however, only upon glycoengineering can it be safely concluded that Lepidoptera will express sialic acid on recombinant glycoproteins [54].…”
Section: Sialic Acidsmentioning
confidence: 99%
“…Frontiers in Cell and Developmental Biology frontiersin.org deuterostomes, and Arthropods (Di et al, 2017;Petit et al, 2018). Interestingly, in the zebrafish Danio rerio, there are two CSS with different substrate specificity and spatial expression one localizing in the nucleus and showing higher specificity towards Neu5Ac and the other localizing to the cytosol and showing higher specificity towards Kdn (Schaper et al, 2012).…”
Section: Sialylation Machinerymentioning
confidence: 99%
“…Subsequent use of Sias depends on their activation to the sugar-nucleotide cytidine monophosphate sialic acid (CMP-sialic acid or CMP-Sia) which is catalyzed by the cytidine monophosphate N -acetylneuraminic acid synthetase or CMP-sialic acid synthetase (CMAS or CSS) in the nucleus of most vertebrate cells ( Figure 2A ). In Metazoa, orthologous sequences of human CMAS gene were retrieved in the Cnidaria, deuterostomes, and Arthropods ( Di et al, 2017 ; Petit et al, 2018 ). Interestingly, in the zebrafish Danio rerio , there are two CSS with different substrate specificity and spatial expression one localizing in the nucleus and showing higher specificity towards Neu5Ac and the other localizing to the cytosol and showing higher specificity towards Kdn ( Schaper et al, 2012 ).…”
Section: Sias Structure and Biosynthesismentioning
confidence: 99%
“…Interestingly, also insects were shown to contain sialic acids and to express corresponding enzymes. [8][9][10][11] Sialic acids were found in some viruses, various bacteria, protozoa, and pathogenic fungi. They are absent in plants and in most animals in the evolutionary tree lower than the echinoderms.…”
Section: Introductionmentioning
confidence: 99%